Design and Build A Photovoltaic and Vertical Savonious Turbine Power Plant as an Alternative Power Supply to Help Save Energy in Skyscrapers - Dadang Priyambodo; Anggara Trisna Nugraha (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2021)
Indonesia is a tropical country, because its area that crosses the equator has enormous solar potential, with a radiation magnitude of 4.80 kWh / m2 / day / day or equivalent to 112,000 GWp. Meanwhile, the solar energy received by the earth is 1.74 x 1017 W / hour, of which about 1-2% is converted into wind energy. However, in terms of total energy potential, Indonesia only uses around 10 MWp of solar energy, the difference is that wind energy which is planned to reach 250 MW in 2025 only uses 1 MW of the total potential. Skyscrapers are places with enormous wind energy potential. Because if the height exceeds 150 m, the reference point of the building can be called a skyscraper, which will cause high wind speed at the top of the building. This phenomenon is caused by the influence of the friction force which suppresses the wind speed, therefore the higher the position, the higher the wind speed. With this potential, to provide additional power and help save energy in existing facilities in the building, a smart photovoltaic and vertical turbine prototype design was created. The prototype design is a combination of weathered turbines and solar panels, the reason for using this type of turbine is because it can rotate at low wind speed (low wind speed) and has a very simple structure. In addition, because it uses a vertical shaft, the generator and gearbox can be placed close to the ground, making maintenance easier. The working principle of this prototype is designed to use a turbine to convert wind energy on the roof of the building into electrical energy, then mix it with electrical energy converted from solar energy by solar panels, so that electrical energy will be more optimal.